Yungcautnguuq nunam qainga tamarmi = All the land's surface is medicine : edible and medicinal plants of southwest Alaska - Fienup-Riordan, Ann; Rearden, Alice; Meade, Marie; Jernigan, Kevin (University of Alaska Press, 2020)
"In this book, close to one hundred men and women from all over southwest Alaska share knowledge of their homeland and the plants that grow there. They speak eloquently about time spent gathering and storing plants and plant material during snow-free months, including gathering greens during spring, picking berries each summer, harvesting tubers from the caches of tundra voles, and gathering a variety of medicinal plants. The book is intended as a guide to the identification and use of edible and medicinal plants in southwest Alaska, but also as an enduring record of what Yup'ik men and women know and value about plants and the roles plants continue to play in Yup'ik lives"--